PROFESSIONAL ETHICS: PROBLEMS OF THEORY AND ETHICAL ASPECTS OF PROFESSIONALISM - Dilorom Ibrahimova (Web of Journals Publishing, 2023)
Every professional is firstly a member of society and a citizen of the state in which they live. For this reason, they must know the rules of civil etiquette in addition to the rules of professional etiquette. This article analyses contemporary notions of the concept, essence and structure of professional ethics, considers its main categories and issues, and establishes its relationship with the general theory of morality.
Keywords: professional ethics, professional morality, professionalism, moral prestige.